Fluorescent Crystals of Zwitterionic Imidazolium Pyridinolates: A Rational Design for Solid‐State Emission Based on the Twisting Control of Proemissive N‐Aryl Imidazolium Platforms. Issue 34 (11th September 2017) - Komiya, Naruyoshi; Yoshida, Atsushi; Zhang, Di; Inoue, Ryo; Kawamorita, Soichiro; Naota, Takeshi
Abstract : The synthesis and structural variations in solid‐state emission of zwitterionic imidazolium pyridinolates are described. N ‐Alkylimidazolium 2‐pyridin‐3‐olate1 exhibits intense blue emission at ambient temperature ( Φ 298 K = 0.44, λ max = 424 nm) in the crystalline state, while phenolate2, another pyridinolate analogue bearing the nitrogen atom at a different position on the pyridine ring3, and N ‐phenylimidazolium ring4 are less emissive ( Φ 298 K = 0.05, 0.05, and 0.04) under the same measurement conditions. Temperature‐dependent emission spectra indicate that crystal1 exhibits high heat‐resistance properties towards emission decay and redshifting thermochromism upon increasing temperature, both of which are in contrast with the heat quenching and blueshift properties of phenolate analogue crystal2 under the same measurement conditions. XRD analysis and DFT calculations revealed that the effect of the 2‐pyridinolate functionality on the specific efficiency and thermochromism in the crystalline‐state fluorescence of imidazolium arenolates arises from specific restriction of molecular rotation and the resultant molecular constraints in the crystals. Abstract : Zwitterionic imidazolium 2‐pyridin‐3‐olates exhibit intense blue emission at ambient temperature in the crystalline state, while other analogues such as 2‐phenolate and 3‐pyridin‐2‐olate are less emissive. XRD analyses and DFT calculations revealed that twisting control of arenolate functionalities is the key to obtaining efficient solid‐state fluorescence of the imidazolium–arenolate dyads.